Performance enhancement of benthic microbial fuel cell by cerium coated electrodes. (1st February 2019) - Imran, Mohammad; Prakash, Om; Pushkar, Priyakant; Mungray, Alka; Kailasa, Suresh Kumar; Chongdar, Shobhana; Mungray, Arvind Kumar
Abstract: The low current and power production limit the extensive application of benthic microbial fuel cell (BMFC) in driving the oceanographic marine instruments. The electrode modification is a promising technique for the enhancement of the power output of BMFC. In this work, cerium was electrochemically reduced on the surface of carbon felt electrodes and characterized by various analytical techniques such as Scanning electron microscopy (SEM), Energy dispersive X-ray spectroscopy (EDX) and Fourier-transform infrared spectroscopy (FTIR). The contact angle experiment revealed that the modified electrode exhibited higher wettability than the unmodified one which leads to an improved microbial adhesion. Cyclic voltammetry (CV) results implied that the modified electrode has a higher capacitance and the Electrochemical impedance spectroscopy (EIS) data suggested a reduction in the internal resistance upon modification. The Tafel plot inferred an enhancement in the kinetic activity which was around 29-fold of the unmodified electrode. A maximum power density of 63.81 mW/m 2 was achieved for the reactor having cerium coated anode and platinum coated cathode while the reactor with cerium coated cathode and the unmodified reactor achieved a value of 26.77 mW/m 2 and 10.94 mW/m 2 respectively. These results suggest that cerium performed better at anode than at cathode. The enhancement in the performance is a synergistic effect of the improvement of the extracellular electron transfer because of the coating of cerium at the anode and the enhanced rate of oxygen reduction reaction as a result of the coating of platinum at cathode. Highlights: The electrode of benthic microbial fuel cell (BMFC) is modified by performing electrochemical deposition of cerium. The modified electrode is found to have higher wettability which favors the microbial adhesion on its surface. The electrochemical results suggest that the modified electrode has enhanced kinetic activity and capacitance. A maximum power density of 63.81 mW/m 2 and 10.94 mW/m 2 was achieved for the modified and unmodified reactors respectively.